Transformation of Learning Management under the Merdeka Curriculum: A Case Study at SMA Negeri 1 Cihaurbeuti - Helmawati, Helmawati; Sukmawati, Nina; Agestiningsih, Veronika Sri; Sultoni, Ilham Aziz (Journal of English Language and Education, 2025)
This study aims to analyse the transformation of learning management through the implementation of the Merdeka Curriculum at SMA Negeri 1 Cihaurbeuti, with a focus on managerial functions that include planning, organising, implementing, and supervising. A qualitative approach was used with a case study method. Data collection techniques include in-depth interviews, participatory observation, and document analysis, with research subjects comprising the school principal, teachers, and curriculum staff. Data validity is ensured through triangulation of sources and methods. The results indicate that SMA Negeri 1 Cihaurbeuti has successfully adopted the principles of the Merdeka Curriculum in managerial practices. The planning process is participatory, learning implementation is oriented towards active student involvement, and supervision is carried out through reflective peer supervision. The main challenges were found in the aspects of teacher competence, technological infrastructure, and community involvement. The strategies implemented include training, strengthening communication, and developing a holistic evaluation system. This transformation shows that strengthening school managerial capacity is key to the successful implementation of the Merdeka Curriculum. Despite challenges, well-planned and collaborative strategies have proven capable of fostering a more adaptive and inclusive learning ecosystem.